From Adult Education to Medicine: Praxis across Disciplines - Christopher J. Godshall (Adult Education Research Conference, 2010)
This paper provides a model based on the literature and personal experience, arguing for direct application of adult education theory to the practice of a profession. Praxis is therefore not confined to the educational approach for the adult educator of professionals.